(untitled) (Eurasian Medical Research Periodical, 2023)
The brain undergoes various secondary changes against the background of chronic damage of arterial blood vessels, atherosclerosis and hypertension. Histochemical staining methods provide reliable information when studying the development of destruction and defragmentation of fibrous structures, which are components of vascular components. In this study, cerebral blood vessels were studied using the Schiff and Van Gieson method. Based on the analysis of the obtained results, it was found that most of the destruction and defragmentation process continues with the accumulation of acidic mucopolysaccharides between the walls of the vessels and sharp swellings between the layers and the decrease of the high pressure tolerance of the vessel wall. As a result, angiosclerosis and angiofibrosis continue with the development of foci.